Correlations between Age, Pain Intensity, Disability, and Tactile Acuity in Patients with Chronic Low Back Pain - Juan Wang; Kangyong Zheng; Jinlong Wu; Rui Wang; Xiao Zhuang; Xueqiang Wang (Pain Research and Management)
Objective. Chronic low back pain is an overwhelming problem for a wide range of people and leads to tactile acuity deficits. We aimed to investigate the correlations among age, pain severity, disability, and tactile acuity in patients with chronic low back pain by using multiple tactile acuity tests. Methods. A total of 58 participants (36.40 ± 14.95 years) with chronic low back pain were recruited, and two-point discrimination, point-to-point test, and two-point estimation were performed on their painful low back areas. The correlations between age, pain intensity, disability, and tactile acuity were characterized with Pearson’s correlation coefficients. Subgroup analyses according to the median values of age, pain intensity, and disability were used to compare the intergroup difference in tactile acuity. Results. Results illustrated significant negative associations among age, pain intensity, disability, and tactile acuity. Subgroup analyses revealed that patients with below-the-median values of age, pain intensity, and disability had better performance in tactile acuity tests than those with above-the-median values. Conclusion. This study indicated that tactile acuity was negatively associated with age, pain intensity, and disability in young patients with chronic low back pain.